Cover Crops with Biofumigation Properties for the Suppression of Plant-Parasitic Nematodes: A Review - Kruger, D.H.M.; Fourie, J.C.; Malan, A.P. (South African Journal of Enology and Viticulture, 2013)
Plant-parasitic nematodes are a problem in vineyards worldwide, with some species acting as vectors of grapevine soil-transmitted viruses. Global pressure on the use of soil-applied chemical nematicides has led to a search for new control options, or for alternative methods to suppress plant-parasitic nematodes as part of integrated pest management. This paper gives valuable background information on the use of cover crops with biofumigation properties for the suppression of plant-parasitic nematodes in vineyards.